2016
DOI: 10.14227/dt230416p6
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Discriminating Dissolution Method for Immediate-Release Soft Gelatin Capsules Containing a BCS Class II Compound

Abstract: The purpose of this study was to develop a robust dissolution procedure for liquid-filled, soft gelatin capsules (SGCs) that can distinguish small but real changes in drug product formulation. SGCs were manufactured using different ratios of fill formulations. The formulations were evaluated by performing dissolution testing on fresh capsules and capsules that were aged at different time points and conditions. USP Apparatus 1 (basket) and 2 (paddle) at rotating speeds of 50, 75, or 100 rpm were used to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…It is important to note that the addition of surfactant to dissolution media can sometimes cause a decrease in the dissolution rates of some drug products, and in some instances can also distort drug peaks during high-performance liquid chromatography (HPLC) analysis ( Figure 7). In a previous study [63], it was found that an immediate-release SGC, containing a poorly soluble drug, loratadine, showed peaks distortion in the presence of SLS. A similar observation of a decrease in the dissolution of gelatin capsules with SLS at lower pH has also been reported by other research groups [107,108].…”
Section: Practical Concepts Of Developing a Dissolution Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…It is important to note that the addition of surfactant to dissolution media can sometimes cause a decrease in the dissolution rates of some drug products, and in some instances can also distort drug peaks during high-performance liquid chromatography (HPLC) analysis ( Figure 7). In a previous study [63], it was found that an immediate-release SGC, containing a poorly soluble drug, loratadine, showed peaks distortion in the presence of SLS. A similar observation of a decrease in the dissolution of gelatin capsules with SLS at lower pH has also been reported by other research groups [107,108].…”
Section: Practical Concepts Of Developing a Dissolution Methodsmentioning
confidence: 96%
“…In previous study, it was shown that the dissolution rate obtained using the paddle method was faster, highly variable at lower time points than those obtained using the basket. In contrast, the data collected using the basket dissolution apparatus showed that the method was more selective and had less variation in terms of API release profile [63]. Table 3 shows examples of SGCs that are commercially available and their dissolution methods.…”
Section: Practical Concepts Of Developing a Dissolution Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…LOR shows a poor water solubility. Thus, many studies suggested the use of 900 mL of dissolution media or/and the addition of surfactant or co-solvent in the dissolution media to fulfill sink conditions (Damian et al, 2016;Song and Shin, 2009;Vlaia et al, 2017). In this study, the sink conditions were not applied due to factors related to the limited volume of the nasal delivery, lack of surfactant on the nasal cavity to be simulated by the dissolution media and to evaluate the effect of the particle size reduction on dissolution and diffusion without any interventions from the surfactant.…”
Section: Effects Of Nanosizing On the Diffusion And Permeability Of Lormentioning
confidence: 99%